Design and Analysis of Hand-guided Semi-mechanized Manure Collection Vehicle for Yaks - Zhang, Lei (International Journal of Mechanical and Electrical Engineering, 2025)
Yak dung has both fuel and ecological value in the plateau areas of China. However, the existing collection methods have problems such as being easily crushed or consuming a large amount of manpower. To this end, this paper designs a semi-mechanized hand-guided yak manure picking vehicle, with a focus on optimizing the picking mechanism. By constructing design variables and constraints, using Matlab to calculate key parameters, and conducting motion analysis based on SolidWorks, the picking efficiency is improved and the labor intensity is reduced.